2017
DOI: 10.1111/epi.13951
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of seizure frequency and lateralization on intratemporal effective connectivity in temporal lobe epilepsy

Abstract: SummaryObjective: Patients with temporal lobe epilepsy (TLE) show brain connectivity changes in association with cognitive impairment. Seizure frequency and lateralization are 2 important clinical factors that characterize epileptic seizures. In this study, we sought to examine an interactive effect of the 2 seizure factors on intratemporal effective connectivity based on resting-state functional magnetic resonance imaging (rsfMRI) in patients with TLE. Methods: For rsfMRI data acquired from 48 TLE patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…This result is concordant with the improvement of cognitive impairment observed after reducing seizure frequency with antiepileptic drugs . Park et al (2018) recently showed that the number of seizures and the lateralization of epilepsy were the main factors impairing verbal memory in TLE . A recent study showed that seizure control was the main factor associated with the improvement of memory and executive functioning after surgery.…”
Section: Discussionsupporting
confidence: 61%
“…This result is concordant with the improvement of cognitive impairment observed after reducing seizure frequency with antiepileptic drugs . Park et al (2018) recently showed that the number of seizures and the lateralization of epilepsy were the main factors impairing verbal memory in TLE . A recent study showed that seizure control was the main factor associated with the improvement of memory and executive functioning after surgery.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, the cognitive consequences of NES can depend on brain maturation at NES onset [4]. However, there is an ongoing debate regarding the causal relation between NES and cognitive impairment [10].…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of executive functions in epileptic children may be caused by a number of factors, such as the underlying lesion and/or its neuro-developmental effects, interictal epileptic activity, the total drug load, drug interactions, and the lack of drive and motivation due to depression [9][10][11][12][13][14]. Recently, impaired executive functions were reported in newly diagnosed drug naïve epileptic children [15].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of each neural mass model that determine the local regional properties can be set through the analysis of individual functional imaging data or through the clinical findings. This personalized modeling approach can be applied to specific diseases, and the developed model could reproduce the pathological characteristics of each patient, such as structural and/or functional alteration of the brain, 17 , 91 93 and predict the effects of various therapeutic interventions via systematic simulations in a patient-specific environment. In this section, we briefly review the personalized modeling studies toward clinical application of epilepsy.…”
Section: Biophysical Modeling-based Approachesmentioning
confidence: 99%
“… 9 13 The possibility of cognitive impairment after surgery caused by the removal or severance of specific brain areas is another important issue to consider. 14 17 …”
Section: Introductionmentioning
confidence: 99%